RANCANG BANGUN APLIKASI UJIAN AKHIR SEMESTER ONLINE UNTUK MENGUKUR PENCAPAIAN KOMPETENSI SISWA SMK NEGERI 1 NGULING - Endang Widia Astuti (STMIK YADIKA BANGIL, 2020)
Abstract : Internet technology plays a role in creating e-learning or distance education. Learning no longer has to be done in class, but from anywhere, as long as the computer used can be connected to the internet. In fact, a person can study at universities in other countries without having to live in the country concerned. Thanks to the internet too, various books in digital form or what are referred to as ebooks or various research results can be obtained easily making it easier for anyone who intends to seek or develop knowledge. Various programs on examinations that have been made, especially those being discussed, are national examinations using the CBT (Computer Based Test) system. This exam program also raises the pros and cons of various parties. For the pros, especially the organizers in this case the government, considers that the online exam saves the budget (less paper) and the distribution of the subject matter is fast and cheap, efficient and can narrow the opportunity for question leakage. As for the cons, it can come from some schools, students and the general public, looking at this online exam is very complicated and difficult to implement. Because it has not made a thorough preparation and seemed to rush. Keywords: CBT (Computer Based Test) system, e-lerning